Strategi Pengembangan Usaha Pada Umkm Keluarga Dalam Menghadapi Perubahan Pasar Pada Pengusaha Bunga Sedap Malam Di Rembang Pasuruan - Ishak Ishak; Khamdan Suriyok; Ninik Churniawati (Institut Teknologi dan Bisnis Yadika, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the national economy, particularly in creating employment opportunities, increasing community income, and promoting regional economic growth. Many MSMEs in Indonesia develop as family businesses that are managed and sustained across generations. This study aims to analyze business development strategies of family-based MSMEs in facing market changes, particularly among night-blooming jasmine (tuberose) entrepreneurs in Rembang District, Pasuruan Regency. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation. The informants include business owners, involved family members, and flower traders or collectors. Data analysis was conducted through data reduction, data display, and conclusion drawing, with triangulation techniques to ensure data validity. The results indicate that business development strategies include maintaining product quality, implementing simple innovations in packaging, and utilizing both traditional and digital marketing methods. Family-based business management provides advantages in cost efficiency and trust, although it still faces limitations in managerial systems. In addition, entrepreneurs encounter several challenges such as price fluctuations, changes in market demand, business competition, and weather-related factors. The study concludes that the success of business development is not only determined by product quality but also by the ability of MSME actors to adapt to market changes through appropriate strategies.